Towards New Promising Discoveries for Lung Cancer Patients: A Selection of Papers from the First Joint Meeting on Lung Cancer of the FHU OncoAge (Nice, France) and the MD Anderson Cancer Center (Houston, TX, USA) - Hofman, Paul (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue of Cancers (Basel) is mainly dedicated to selecting papers from the talks given during the first Joint Meeting on Lung Cancer (JMLC) between the MD Anderson Cancer Center (Houston, Texas USA) and the Hospital University Federation (HUF) OncoAge (University Côte d'Azur, Nice, France) (Nice, September 2018). The central theme of JMLC is to discuss new advances and exchange ideas regarding lung cancer. Notably, the talks covered different topics on new therapeutic strategies (targeted therapy and immuno-oncology), molecular and cellular biology, biomarkers, and the epidemiology of lung cancer. Special attention was also given to lung cancer in elderly patients. The articles published in this Special Issue covered subjects such as the assessment of new biomarkers and new approaches for the early detection of lung cancer, epidemiological data, and emphasized a place for the newly characterized cellular pathways in lung cancer, which opens room for therapeutic perspectives for lung cancer patients.